Pengaruh lanjutan substitusi ampas tahu pada pakan basal (BR-2) terhadap penampilan ayam broiler umur 4-6 minggu (fase finisher) - Herlinae Herlinae; Yemima Yemima; Gajo Priyono (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2017)
This study aims to determine the effect of continued substitution of tofu on basal feed (BR-2) on the performance of broiler chickens at the age of 4-6 weeks (Phase Finisher), and to determine the level of substitution of tofu on basal feed (BR-2) to giving the appearance of broiler chickens at the age of 4-6 weeks (Phase Finisher). The study was conducted using completely randomized design (CRD) with A = 100% treatment of basal feed (BR-2), B = 15% + 85% tofu basal feed (BR -2), C = 30% + 70% tofu basal feed (BR-2), and D = 45% + 55% tofu basal feed (BR-2), each treatment was repeated 5 times so that there are 20 units trial. Variable observed included weight gain, feed intake, and feed conversion. The results showed substitution of tofu on a basal feed affect the appearance, that were body weight gain, feed intake. and feed conversion at the age of 4 weeks. No effect on feed conversion at the age of 5 and 6 weeks. Treatment A and treatment B were able to give the appearance of good growth.